(untitled) (TAJ: Journal of Teachers Association, 2009)
The study was carried out to observe the changes in lung functions in the elderly women both before and two months after supplementation of vitamin A. For this purpose, a total number of 30 apparently healthy elderly female subjects with age ranging from 40-60 years were selected from a rural area of Bangladesh. They were studied both before and two months after supplementation of vitamin A at a dose of 10,000 IU daily. Sex matched 30 apparently healthy adult subjects with age ranging from 25-40 years were taken as control. Pulmonary functions were assessed by measuring FVC, FEVi, FEVi/FVC% and PEFR by VM1 ventilometer on standing position. The mean measured pulmonary variables such as FVC, FEVi, FEV,/FVC% and PEFR were lower than those of their predicted values both in the experimental and control groups. The mean measured values of all the pulmonary variables were significantly lower in the elderly subjects compared with those of the younger age group. Again, the FVC, FEVi, FEVi/FVC% and PEFR were significantly increased in the same group of subjects after supplementation of vitamin A. But not up to the level of those of younger subjects. The result of the study reveals that pulmonary functions become lower in the elderly subject’s improvement of which occurs after supplementation of vitamin A. These lower pulmonary functions in the elderly subjects of the present study group is likely to be due to low dietary intake of vitamin A as pulmonary functions were improved after supplementation of vitamin A. doi: 10.3329/taj.v16i2.3886 TAJ December 2003; Vol.16(2): 68-72